SURGICAL TREATMENT AND PROPHYLAXIS OF PROLAPSE OF GENITALS IN DIFFERENT AGE GROUPS - Ilnur I. Musin; Albina G. Imelbayeva; Elvira R. Mehtiyeva (Креативная хирургия и онкология, 2017)
Introduction. According to WHO up to 50-60% of women in postmenopause suffer from prolapse of genitalia. Wherein as a rule this state is accompanied with a number of anatomic and functional disorders: primarily obstructive uresis or enuresis, overactive bladder, defecatory disorder, gamic disorder, and also permanent sense of discomfort and heaviness in perineal region. In connection therewith, the main objective of the research was to evaluate the results of surgical correction of genital prolapse using differentiated approaches to the management through up-to-date methods to morphologically assess the device that immobilize the uterus.Materials and methods. The article presents the results of a study of 203 patients with genital prolapse II-IY stages, which were divided into 2 groups: the first group included 45 patients of reproductive age from 35 to 45 years, and the second group consisted of 158 patients, aged 45 to 60 years, who underwent pelvic floor reconstruction, vaginal hysterectomy with the use of endoscopic techniques in combination with urethropexies mesh material, salvageable, including using titanium metallicity. As to justify surgical correction, patients in the second group were conducted histological analysis of the round uterine ligaments, the cardinal ligaments of the uterus and the Sacro-uterine ligaments. Patients were examined after 6, 12, 24, 36 months after the complex treatment.Results. It was found that in patients of reproductive age with unfulfilled reproductive function of type of surgical treatment is considered only in combination with urethropexies mesh or collagen material.Conclusion. To reduce the risk posthysterectomy prolapse requires a comprehensive diagnostic anatomical and functional disorders of pelvic organs and pelvic diaphragm in the preoperative period, which determines the access, the scope of surgical intervention and allows to minimize both operational and postoperative complications.